Electronic parameters in cobalt-based perovskite-type oxides as descriptors for chemocatalytic reactions - Johannes Simböck (Nature Portfolio, 2020)
Design of efficient catalysts requires understanding the decisive electronic parameters for catalytic efficacy and their dependence on elemental composition. Here, the authors report covalency as suitable descriptor of perovskite-type transition metal oxides as chemo-catalysts.